Analysis of Quantization Noise and Power Estimation of Continuous-Time Delta Sigma Analog-to-Digital Converter Using Test Enable Feature For 4G Radios - Anil Kumar Sahu; Vivek Kumar Chandra; G R Sinha (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
This paper presents a novel approach for completely test enable feature and low-voltage delta– sigma analog-to-digital (A/D) converters for cutting edge wireless applications. Oversampling feature of ADCs and DACs is enough to meet the requirement related to in-band and adjacent channel leakage ratio (ACLR) execution of 3G/4G portable radio. The quantization noise which is not filtered in ADC is addressed. We have achieved work power-optimization and test enable feature of oversampling ADC is uses in design and simulation so that the problem of quantization error in continues time sigma delta ADC is solved. This paper suggests support to designer for selecting appropriate topologies with various channel arrangements, number of bits and oversampling issues. A test enable feature of CT A/D is presented introducing the test signal generation (TSG) and the COrdinate Rotation Digital Computer (CORDIC) for evaluating the performance of ADC. This helps in addressing the challenge of 4G and upcoming 5G wireless radio. System level plan of a delta–sigma modulator ADC for 4G radios is studied.